Plasmacytoid dendritic cell‐derived IFN‐α promotes murine liver ischemia/reperfusion injury by induction of hepatocyte IRF‐1. Issue 1 (27th May 2014) - Castellaneta, Antonino; Yoshida, Osamu; Kimura, Shoko; Yokota, Shinichiro; Geller, David A.; Murase, Noriko; Thomson, Angus W.
<x xml:space="preserve">Abstract</x> Plasmacytoid dendritic cells (pDC) constitute the body's principal source of type I interferon (IFN) and are comparatively abundant in the liver. Among various cytokines implicated in liver ischemia and reperfusion (I/R) injury, type I IFNs have been described recently as playing an essential role in its pathogenesis. Moreover, type I IFNs have been shown to up‐regulate hepatocyte expression of IFN regulatory factor 1 (IRF‐1), a key transcription factor that regulates apoptosis and induces liver damage after I/R. Our aim was to ascertain the capacity of IFN‐α released by liver pDC to induce liver damage through hepatic IRF‐1 up‐regulation after I/R injury. Our findings show that liver pDC mature and produce IFN‐α in response to liver I/R. Liver pDC isolated after I/R induced elevated levels of IRF‐1 production by hepatocytes compared with liver pDC isolated from sham‐operated mice. Notably, hepatic IRF‐1 expression was reduced significantly by neutralizing IFN‐α. In vivo, IFN‐α neutralization protected the liver from I/R injury by reducing hepatocyte apoptosis. This was associated with impaired expression of IRF‐1 and proapoptotic molecules such as Fas ligand, its receptor (Fas) and death receptor 5, which are regulated by IRF‐1. Furthermore, pDC‐depleted mice failed to up‐regulate hepatic IFN‐α and displayed less liver injury associated with reduced levels of hepatic interleukin (IL)‐6, tumor necrosis factor‐α, and hepatocyte apoptosis after I/R compared with controls. Conclusion: these data support the hypothesis that IFN‐α derived from liver pDC plays a key role in the pathogenesis of liver I/R injury by enhancing apoptosis as a consequence of induction of hepatocyte IRF‐1 expression. (Hepatology 2014;60:267–277)